2007
DOI: 10.1021/ma062230p
|View full text |Cite
|
Sign up to set email alerts
|

Monodisperse Silica Particles Grafted with Concentrated Oxetane-Carrying Polymer Brushes:  Their Synthesis by Surface-Initiated Atom Transfer Radical Polymerization and Use for Fabrication of Hollow Spheres

Abstract: An oxetane group-carrying methacrylate, 3-ethyl-3-(methacryloyloxy)methyloxetane (EMO), was polymerized via copper-mediated atom transfer radical polymerization (ATRP) initiated from the surface of monodisperse silica particles (SiPs). The polymerization proceeded in a living manner producing SiPs grafted with well-defined poly(EMO) (PEMO) of target molecular weight up to about 400K with a graft density as high as 0.36 chains/nm 2 . The surface-initiated ATRP of methyl methacrylate (MMA) with PEMO-grafted SiPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 66 publications
2
92
0
Order By: Relevance
“…As mentioned above, in order to achieve a better effect, the halogen exchange technique was also utilized in the polymerization processes, although the effect was not evident in our experiments. In addition, a more severe reaction conditions of bulk 29 than solvent conditions was used based on the consideration of that the reaction was the second one. The synthetic conditions and the results were summarized in Table II.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, in order to achieve a better effect, the halogen exchange technique was also utilized in the polymerization processes, although the effect was not evident in our experiments. In addition, a more severe reaction conditions of bulk 29 than solvent conditions was used based on the consideration of that the reaction was the second one. The synthetic conditions and the results were summarized in Table II.…”
Section: Resultsmentioning
confidence: 99%
“…Fukuda et al reported the ring-opening reactivity of oxetane for the shell crosslinking of the poly(3-ethyl-3-(methacryloyloxy)methyloxetane) (PEMO) grafted silica templates (740 nm) via SI-ATRP. 20 The diameter of the microcapsules obtained was about 1.5 m.…”
Section: Introductionmentioning
confidence: 92%
“…Ten Previously the M n of the graft and free polymers produced in the same batch were found to be nearly the same [51]. Assuming that all the monomers consumed were converted to the polymer, the M n,conv value was determined from the conversion evaluated by 1 HNMR.…”
Section: Measurements Of Contact Anglesmentioning
confidence: 98%